The Urban Planning of Surabaya City with The Aim of Creating a Green City - Anggraini, Yusnia Dwi; Sukmana, Selamet Jaya; Sulistyowaty, Dewi; Rohmiah, Faizahtur; Rasidi, Harriadi (Journal of Civil Engineering, Planning and Design, 2024)
Surabaya is the second largest city in Indonesia, with a population of 2,987,863 individuals as of 2022. The presence of a large population inevitably leads to an increase in both environmental impacts and societal needs. The high population in Surabaya city will result in significant environmental impacts due to human activities. The increase in population size has resulted in a corresponding increase in the demand for land to accommodate the development of infrastructure necessary to meet the needs of urban residents. This development often involves the displacement and conversion of existing green spaces into built-up areas, leading to a reduction in the availability of green spaces within the city